Inquiry Learning Model to Improve Student Cognitive Learning Outcomes in Temperature and Heat - Hikmawati Hikmawati; Kusmiyati Kusmiyati; Sutrio Sutrio (Postgraduate, University of Mataram, 2020)
This study aims to describe the effectiveness of the inquiry learning model to improve students' cognitive learning outcomes at the temperature and heat of class XI from one public school (SMAN 1 Gerung). This type of research is a quasi experiment with the basic pattern